Further studies on the fairy shrimp genus Branchinella (Crustacea: Anostraca: Thamnocephalidae) in Australia, with descriptions of five new species - Timms, Brian V (Zootaxa, 2012)
Branchinella is the most speciose anostracan genus in Australia and is one of a few speciose fairy shrimp genera in theworld. Two new species, B. erosa sp. nov. and B. hearnii sp. nov. live in hyposaline waters in western Western Australiaand three new species, B. herrodi sp. nov., B. anatinorhyncha sp. nov. and B. minmina sp. nov. are described from freshwaters in northern Queensland. Branchinella clandestina is synonymised with B. affinis, so that the total Australian spe-cies of Branchinella is now 39. Significant new distribution records are given for B. affinis, B. compacta and B. simplex.New morphological data is provided for B. compacta and B. wellardi to differentiate them from B. hearnii sp. nov. and B.herrodi sp. nov. respectively. Branchinella compacta and B. hearnii sp. nov. may demonstrate lock and key amplexus, while multiple tumidities on female B. erosa sp. nov. suggest possible sensory selection by males.